Time-Prolonged Release of Tumor-Targeted Protein–MMAE Nanoconjugates from Implantable Hybrid Materials - Naroa Serna; Aïda Falgàs; Annabel García-León; Ugutz Unzueta; Yáiza Núñez; Alejandro Sánchez-Chardi; Carlos Martínez-Torró; Ramón Mangues; Esther Vazquez; Isolda Casanova; Antonio Villaverde (Pharmaceutics, 2022)
The sustained release of small, tumor-targeted cytotoxic drugs is an unmet need in cancer therapies, which usually rely on punctual administration regimens of non-targeted drugs. Here, we have developed a novel concept of protein–drug nanoconjugates, which are packaged as slow-releasing chemically hybrid depots and sustain a prolonged secretion of the therapeutic agent. For this, we covalently attached hydrophobic molecules (including the antitumoral drug Monomethyl Auristatin E) to a protein targeting a tumoral cell surface marker abundant in several human neoplasias, namely the cytokine receptor CXCR4. By this, a controlled aggregation of the complex is achieved, resulting in mechanically stable protein–drug microparticles. These materials, which are mimetics of bacterial inclusion bodies and of mammalian secretory granules, allow the slow leakage of fully functional conjugates at the nanoscale, both in vitro and in vivo. Upon subcutaneous administration in a mouse model of human CXCR4+ lymphoma, the protein–drug depots release nanoconjugates for at least 10 days, which accumulate in the tumor with a potent antitumoral effect. The modification of scaffold cell-targeted proteins by hydrophobic drug conjugation is then shown as a novel transversal platform for the design of slow releasing protein–drug depots, with potential application in a broad spectrum of clinical settings.